Blood Pressure Reduction in Patients with Hypertension Through Soursop Leaf Tea Consumption - Siagian, Masryna; Hulu, Victor Trismanjaya; Ginting, Rapael; Manalu, Putranto; Sijabat, Vina Helsa Laora; Tarigan, Nita Kastrina (Althea Medical Journal, 2024)
Background: Controlling hypertension through pharmacological treatment is effective but can potentially lead to long-term side effects. Thus, more patients with hypertension have turned to herbal plants for treatment. The objective of this study was to examine the effectiveness of soursop leaf tea in reducing blood pressure in patients with hypertension.Methods: This study employed a quasi-experimental approach with a non-randomized pretest-posttest control group design, involving 30 participants in the intervention group and 30 participants in the control group. Data was analyzed using the Wilcoxon test to assess the disparity in mean blood pressure levels before and after consumption of soursop leaf tea. The Mann-Whitney test was used to examine the distinction in mean blood pressure between the intervention group and the control group.Results: In the intervention and control groups, most respondents were aged 56–65 years (60% and 66.7%), male (70% and 56.7%) and had suffered from hypertension for more than 5 years (70% and 56.7%). There was a significant difference in systolic blood pressure (p<0.001) and diastolic blood pressure (p<0.001) before and after the administration of soursop leaf tea. The mean systolic and diastolic blood pressure in the intervention group decreased significantly compared to the control group (p<0.001).Conclusions: Consumption of soursop leaf tea can reduce systolic and diastolic blood pressure, suggesting that this local herb has a potential effect on individuals diagnosed with hypertension.